Systematic experimental investigation to support the development of seismic performance factors for cross laminated timber shear wall systems. (1st October 2018) - Amini, M. Omar; van de Lindt, John W.; Rammer, Douglas; Pei, Shiling; Line, Philip; Popovski, Marjan
Highlights: Quasi-static cyclic tests were conducted on CLT shear walls to study some parameters. Boundary condition has a slightly beneficial effect on the CLT wall behaviour. Both stiffness and strength increase as the gravity load increases. Panel thickness has only a slight effect on wall stiffness and strength. Panel aspect ratio and vertical joints affect stiffness and deformation capacity. Abstract: In the US, codified seismic design procedure requires the use of seismic performance factors which are currently not available for CLT shear wall systems. The study presented herein focuses on the determination of seismic design factors for CLT shear walls in platform type construction using the FEMA P-695 process. Results from the study will be proposed for implementation in the seismic design codes in the US. The project approach is outlined and selected results of full-scale shear wall testing are presented and discussed. Archetype development, which is required as part of the FEMA P-695 process, is briefly explained with an example. Quasi-static cyclic tests were conducted on CLT shear walls to systematically investigate the effects of various parameters. The key aspect of these tests is that they systematically investigate each potential modelling attribute that is judged within the FEMA P-695 uncertainty quantification process. Boundary constraints and gravity loading were both found to have a beneficial effect on the wall performance, i.e. higher strength and deformation capacity. Higher aspect ratio panels (4:1) demonstrated lower stiffness and substantially larger deformation capacity compared to moderate aspect ratio panels (2:1). However, based on the test results there is likely a lower bound for aspect ratio (at 2:1) where it ceases to benefit deformation capacity of the wall. This is due to the transition of the wall behaviour from rocking to sliding. Phenomenological models were used in modelling CLT shear walls. Archetype selection and analysis procedure was demonstrated and nonlinear time history analysis was conducted using different wall configurations.